1953
DOI: 10.1055/s-0028-1131247
|View full text |Cite
|
Sign up to set email alerts
|

Zur Entstehung des Morbus Basedow

Abstract: J. M eis s n e r Aus der Fülle der ungelösten Probleme, die dem Kliniker bei der Berührung mit der Hyperthyreose entgegentreten, ist die Frage nach dem Wirkungsmechanismus der antithyreoidalen Substanzen besonders wichtig.Der Jodstoffwechsel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1954
1954
1971
1971

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In contrast to these observations in wild rats, studies in mice exposed to acute defeat for 2, 4, 8, and 16 days showed a significant increase in plasma TSH concentrations and a continual rise in pituitary TSH levels indicating that exposure to repeated defeat may increase the synthesis, release, and storage of TSH (Eleftheriou et a1., 1968). These observations with mice coincide with previous studies in wild rabbits following capture (Eickhoff, 1949, andKracht &Kracht, 1952) who report intense overactivity of the pituitary-thyroid system coupled with autonomic instability within a few weeks after capture. Exposure of captive wild rabbits to their predators (ferrets, dogs, and man) is also a sufficient stimulus to elicit a thyrotoxic response.…”
Section: Effects Of Aggression On Hormonessupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast to these observations in wild rats, studies in mice exposed to acute defeat for 2, 4, 8, and 16 days showed a significant increase in plasma TSH concentrations and a continual rise in pituitary TSH levels indicating that exposure to repeated defeat may increase the synthesis, release, and storage of TSH (Eleftheriou et a1., 1968). These observations with mice coincide with previous studies in wild rabbits following capture (Eickhoff, 1949, andKracht &Kracht, 1952) who report intense overactivity of the pituitary-thyroid system coupled with autonomic instability within a few weeks after capture. Exposure of captive wild rabbits to their predators (ferrets, dogs, and man) is also a sufficient stimulus to elicit a thyrotoxic response.…”
Section: Effects Of Aggression On Hormonessupporting
confidence: 89%
“…Exposure of captive wild rabbits to their predators (ferrets, dogs, and man) is also a sufficient stimulus to elicit a thyrotoxic response. In addition, Kracht and Kracht (1952) and Bansi et al(1953) noted that the response to predators could be abolished by either removing the thyroid or inhibiting the secretion of thyroid hormones with thiouracil. The observations with wild rabbits point to the fact that the psychological threat of injury might, in some case, lead to unrestrained secretion of TSH and it may be caused by the failure of adrenocortical steroids to inhibit TSH secretion (Harris & Woods, 1958).…”
Section: Effects Of Aggression On Hormonesmentioning
confidence: 99%
“…21 Timid wild rabbits with highly labile autonomic nervous systems may exhibit typical hyperthyroidism if exposed to fright situations; capture alone may elicit severe shock and even sudden death. 22 Death from a "broken heart," although always regarded with utmost skepticism, could never be rejected as a possibility. Sudden, unexpected and anatomically unexplained deaths after an emotional shock, after slight bodily punishment accompanied by hostile resentment and a sense of humiliation, or in a state of great fright have occasionally been reported.…”
Section: Deatlu Which Are Unexplainable Both Clinicauy and At Autop•ymentioning
confidence: 98%